Suboptimal light conditions negatively affect the heterotrophy of Planktothrix rubescens but are beneficial for accompanying Limnohabitans spp - Horňák, Karel; Zeder, Michael; Blom, Judith F; Posch, Thomas; Pernthaler, Jakob (Environmental microbiology, 2012)
We examined the effect of light on the heterotrophic activity of the filamentous cyanobacterium Planktothrix rubescens and on its relationship with the accompanying bacteria. In situ leucine uptake by bacteria and cyanobacteria was determined in a subalpine mesotrophic lake, and natural assemblages from the zone of maximal P. rubescens abundances were incubated for 2 days at contrasting light regimes (ambient, 100× increased, dark). Planktothrix rubescens from the photic zone of the lake incorporated substantially more leucine, but some heterotrophic activity was maintained in filaments from the hypolimnion. Exposure of cyanobacteria to increased irradiance or darkness resulted in significantly lower leucine incorporation than at ambient light conditions. Highest abundances and leucine uptake of Betaproteobacteria from the genus Limnohabitans were found in the accompanying microflora at suboptimal irradiance levels for P. rubescens or in dark incubations. Therefore, two Limnohabitans strains (representing different species) were co-cultured with axenic P. rubescens at different light conditions. The abundances and leucine incorporation rates of both strains most strongly increased at elevated irradiance levels, in parallel to a decrease of photosynthetic pigment fluorescence and the fragmentation of cyanobacterial filaments. Our results suggest that Limnohabitans spp. in lakes might profit from the presence of physiologically stressed P. rubescens.
Keywords: Darkness; Cyanobacteria; tma; světlo; Heterotrophic Processes; Leucine; Water Microbiology; Photosynthesis; jezera; mikrobiologie vody; sinice; Light; leucin; heterotrofní procesy; Lakes; fotosyntéza; Comamonadaceae